HUBUNGAN PERILAKU MAKAN DAN STATUS GIZI DENGAN STATUS KESEHATAN MENTAL SISWA SEKOLAH DASAR - Vera Adi, Jufriana Yuwono; Mangalik, Gelora; Ranimpi, Yulius Yusak (Politeknik Kesehatan Tanjung Karang, 2020)
Nutrition is one of the important factors that determine the level of health between physical and mental development. Well greatly affects the concentration and intelligence of children in receiving and absorbing any knowledge obtained at school. The purpose of this study was to identify the relationship between eating behavior and nutritional status with the mental health status of students in Jayapura State Instruction Waena Permai. This research uses quantitative methods with correlation design and data collection techniques used questionnaires and structured interviews. Respondents in this study were all students in grades V and VI with age criteria 10-13 years with a sample of 40 respondents. The result of this study was, the eating behavior of class V and VI respondents most often consumed rice, eggs, fish, water spinach, bananas, and sweet tea. Nutritional status in class V and VI respondents was normal, and most mental health in class V and VI respondents was abnormal. In the conclusion of this study, there is no significant relationship between nutritional status and mental health with a significant value of 0.949.